Respostas

2012-12-19T13:03:58-02:00

P.A: Os termos de uma PA segue uma razão que é somada ao termo posterior e subtraída do anterior:

 

(a-r) + a + (a+r) = 21;

a + a + a + r - r = 21;

3a = 21;

a = 7;

 

(a-r) * a * (a+r) = 315;

(7-r) * 7 * (7+r) = 315;

(49 - r^2)*7 = 315;

(49 - r^2) = 315/7;

(49 - r^2) = 45

 - r^2 = 45 - 49;

 - r^2 = -4;

  r^2 =4

r = raiz quadrada (4);

r = +/- 2;

 

PA Crescente: (5,7,9);

PA Decrescente: (9,7,5);

2 3 2
2012-12-19T13:49:28-02:00

bom

(a-r) + a + (a+r) = 21;

a + a + a + r - r = 21;

3a = 21;

a = 7;

 

(a-r) * a * (a+r) = 315;

(7-r) * 7 * (7+r) = 315;

(49 - r^2)*7 = 315;

(49 - r^2) = 315/7;

(49 - r^2) = 45

 - r^2 = 45 - 49;

 - r^2 = -4;

  r^2 =4

r = raiz quadrada (4);

r = +/- 2;

 

PA Crescente: (5,7,9);

PA Decrescente: (9,7,5);

1 5 1